2020
DOI: 10.3389/fcell.2020.580824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of HRE-Regulated VEGF Expression and Transfection on Neural Stem Cells in Rats

Abstract: In this study, we analyzed neural stem cells transfected with the HRE-VEGF gene in groups experiencing different periods of hypoxia. The results of RT-PCR showed that the expression of vascular endothelial growth factor (VEGF) mRNA gradually increased with the prolonged period of hypoxia (p < 0.05). The results from the western-blot test showed that expression of the VEGF protein increased with as the period of hypoxia increased (p < 0.05). The results of MTT combined with Elisa reagent showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many researches have reported that overexpressed NGF is latently oncogenic and possesses other risks [ 51 , 52 ], and thus needed appropriate regulators to improve the specificity of NGF overexpression. HRE is induced explicitly by hypoxia-inducible factors in hypoxia sites [ 53 ]; thereupon, according to injury conditions, we hope to regulate the expression of NGF so that an appropriate amount of NGF could be expressed explicitly at hypoxia sites and prevent latent hyperplasia or other side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches have reported that overexpressed NGF is latently oncogenic and possesses other risks [ 51 , 52 ], and thus needed appropriate regulators to improve the specificity of NGF overexpression. HRE is induced explicitly by hypoxia-inducible factors in hypoxia sites [ 53 ]; thereupon, according to injury conditions, we hope to regulate the expression of NGF so that an appropriate amount of NGF could be expressed explicitly at hypoxia sites and prevent latent hyperplasia or other side-effects.…”
Section: Discussionmentioning
confidence: 99%